Community Perceptions of Whale Shark (Rhincodon typus) Conservation in the Coastal District of Yaur Nabire, Papua - Tipagau, Otniel; Rapi, Nuraeni L.; Cahyono, Indra (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Conservation and management of resources that have an economic impact on the community will save the shark population in the Cendrawasih Bay Marine Park. Therefore, the government needs to implement conservation management efforts and limit shark catches. The aim of this research is to determine public perceptions regarding the conservation of whale sharks (Rhincodon Typus) on the coast of Yaur district, Nabire district. Data collection techniques used at the research location are: Observation, interviews, and documentation of activities. Data obtained from observations and distribution of questionnaires were processed using Microsoft Excel software. The results of the processed data are displayed in the form of tables, graphs or diagrams. The results of the research show that the perception of coastal communities in Yaur district towards the conservation of whale sharks (Rhincodon typus) is positive with the dominant percentage knowing about shark conservation and infrastructure. Communities in the Coastal Yaur District actively participate in the conservation of whale sharks (Rhincodon typus) and maintain and maintain infrastructure.